Microstructural tailoring and enhancement in compressive properties of additive manufactured ti-6al-4v alloy through heat treatment - Ahn, Byungmin (Materials, 2021)
Among laser additive manufacturing, selective laser melting (SLM) is one of the most popular methods to produce 3D printing products. The SLM process creates a product by selectively dissolving a layer of powder. However, due to the layerwise printing of metal powders, the initial microstructure is fully acicular α′-martensitic, and mechanical properties of the resultant product are often compromised. In this study, Ti-6Al-4V alloy was prepared using SLM method. The effect of heat treatment was carried out on as-built SLM Ti-6Al-4V alloy from 650–1000◦C to study respective changes in the morphology of α/α′-martensite and mechanical properties. The phase transition temperature was also analyzed through differential thermal analysis (DTA), and the microstructural studies were undertaken by optical microscopy (OM) and scanning electron microscopy (SEM). The mechanical properties were assessed by microhardness and compressive tests before and after heat treatment. The results showed that heat treated samples resulted in a reduction in interior defects and pores and turned the morphology of the α′-martensite into a lamellar (α + β) structure. The strength was significantly reduced after heat treatment, but the elongation was improved due to the reduction in columnar α′-martensite phase. An optimum set of strength and elongation was found at 900◦C.
Keywords: % reductions; 3-D printing; 3D-printing; After-heat treatment; Compressive properties; Implant; Laser additive manufacturing; Microstructural tailoring; Selective laser melting; Ti-6Al-4V alloy; Additive manufacturing; Annealing; Biomaterials; Implants; Powder metallurgy; Selective laser melting; Titanium